2005
DOI: 10.1073/pnas.0507394102
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic transport of SNARE proteins in the Golgi apparatus

Abstract: Localization of a membrane protein in a subcellular compartment can be achieved by its retention in the compartment or by its continuous transport toward this compartment. Previous results have suggested that specific enzymes are localized in the Golgi apparatus at least in part by selective retention and exclusion from transport vesicles. However, the function of some Golgi SNARE (soluble N-ethylmaleimide-sensitive factor attachment protein receptor) proteins is not compatible with their exclusion from transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 23 publications
(22 reference statements)
3
18
0
Order By: Relevance
“…SNARE proteins behave differently in the gradient upon different treatments. For example, Bet1 was found to be enriched in the vesicle fractions, regardless of the presence of mitotic kinases, consistent with the previously described data that it is a recycling SNARE protein in the cell (36,37). Gos28, a Golgi t-SNARE, was not found in the vesicles under interphase conditions, but it was slightly enriched in the vesicles in the presence of mitotic kinases.…”
Section: Resultssupporting
confidence: 78%
“…SNARE proteins behave differently in the gradient upon different treatments. For example, Bet1 was found to be enriched in the vesicle fractions, regardless of the presence of mitotic kinases, consistent with the previously described data that it is a recycling SNARE protein in the cell (36,37). Gos28, a Golgi t-SNARE, was not found in the vesicles under interphase conditions, but it was slightly enriched in the vesicles in the presence of mitotic kinases.…”
Section: Resultssupporting
confidence: 78%
“…It is, however, probable that selective exclusion of membrane proteins occurs at every step of intracellular transport. During an earlier analysis of intra-Golgi transport, we indeed observed that resident Golgi proteins are less abundant at sites where vesicles form (the rims of cisternae), suggesting at least partial exclusion from transport vesicles (Cosson et al, 2002;Cosson et al, 2005;Orci et al, 2000). Similarly, we reported selective membrane exclusion during the formation of phagocytic or macropinocytic cups in Dictyostelium cells (Mercanti et al, 2006).…”
Section: Fig 4 Transmembrane Domains Control Exclusion From Clathrisupporting
confidence: 54%
“…The presence of GS15 on all cisternae permits this SNARE complex to mediate homotypic membrane fusion. Interestingly, although the SNAREs needed for endoplasmic reticulum to Golgi transport are localized exclusively at the rims of Golgi cisternae, GS15 and Syntaxin 5 are only 2-fold enriched at that location and are also seen in the middle of cisternae (38). Thus, the SNAREs proposed to mediate homotypic fusion are found precisely where they may be needed for more local fusion events.…”
Section: Combining Premises 1 Andmentioning
confidence: 98%